Problem Based Learning: Can it improve football passing skills? - Wendy Arizona; Destriana Destriana; Imam Kurniawan (Sriwijaya Journal of Sport, 2024)
Research Problems: Good passing not only helps maintain possession of the ball but also supports the team's overall strategy. However, many players, especially at the beginner or school-age level, often face difficulties in passing with accuracy, power and timing. Research Objectives: This study aims to enhance students' football passing skills by implementing teaching styles based on Problem-Based Learning (PBL) at State Junior High School 15 in Palembang. Methods: The research employed Classroom Action Research (CAR) with 32 seventh-grade students as subjects. Data were collected through passing skill tests conducted before and after the intervention and observational participation during the learning process. Results: The findings indicate that applying this learning-based teaching style improved students' passing skills. In the first cycle, only 33% of the students met the Minimum Completion Criteria (MCC). However, after the second cycle, 100% of the students achieved scores above the MCC, with an increase in the average score from 72.84 to 87.50. Conclusion: These results demonstrate that a learning-based teaching style is effective in enhancing students' technical skills and tactical understanding of football.